Modal characteristics and fluid–structure interaction vibration response of submerged impeller. (August 2022) - Huo, Shihui; Huang, Hong; Huang, Daoqiong; Liu, Zhanyi; Chen, Hui
Turbo pump is one of the elements with the most complex flow of liquid rocket engine, and as an important component of turbo pump, an impeller is the weak point affecting its reliability. In this study, a noncontact modal characteristic identification technique was proposed for the liquid oxygen pump impeller. Modal characteristics of the impeller under three different submerged media, air, pure water, and brine with same density as liquid oxygen, were tested based on the noncontact modal identification technology. Submersion state directly affects the modal frequencies and damping ratio. The transient vibration response characteristics of the impeller excited by the unsteady flow field was achieved combining with unsteady flow field analysis and transient dynamic analysis in the whole flow passage of the liquid oxygen pump. Vibration responses at different positions of the impeller show 10X and 20X frequencies, and the amplitude at the root of short blade is significant, which needs to be paid more attention in structural design and fatigue evaluation.